Power improvement of wind turbine based on maximum power point tracking (MPPT) controller / Zulina Zulkifeli - Zulina, Zulkifeli (2018)
This thesis presents a modern controller for simulation of maximum power point tracking (MPPT) technique using boost converter for wind energy conversion system. It uses output voltage as feedback to regulate its output voltage to a desired value without steady state oscillations with the aid of Matlab ® & Simulink ® simulationc software. The methodology is proposed by using modern controller for application of boost DC-DC converter system. It is implemented on the boost converter system by applying state space method. Modern controllers are simulated in closed loop system which consists of state feedback controller, optimal controller, stae feeedback with feed foward controller and integral controller. These modern controllers are simulated to analyze transient responseand percentage of overshoot form boost converter output voltage. If the output system is observable, a full state observer can be implemented. All controllers are compared, which from this work it is proof that state feedback controller at Poles 250 is the best controller, whereby produces less error it is 0.002V error.